The Relationship Between Self-Control and Aggressive Behavior in SMAN 1 Tumpang - Rachmadianti, Annisa Putri; Kamila, Nilna Maulidya; Nazzarudin, Muhammad Kholid; Prihatiningsih, Riskiyana (Universitas Negeri Malang, 2024)
This research was motivated by aggressive behavior that occurred in students at SMA Negeri 1 Tumpang. Based on data obtained in the field, 12.8% of students carried out aggressive actions both verbally and non-verbally. This happens during learning activities or outside learning activities. The aim of this research is to determine the relationship between self-control and aggressive behavior of students at SMA Negeri 1 Tumpang. This research used a correlational quantitative approach method with a sample of 179 students using proportional random sampling techniques. Research data collection used a self-control scale and an aggressive behavior scale. Based on these results , it was found that there was a sufficient relationship between the self-control variable and the aggressive behavior variable in students at SMA Negeri 1 Tumpang. From these results, it was concluded that there was a positive correlation, then students' aggressive behavior and self-control had the same direction, so that if students' self-control was high then students' aggressive behavior was also high